Literal Reading Difficulties among freshmen Indonesian EFL Students: A Survey-Based Investigation - Herman Resyadi; Ferawaty Syam (Teaching English and Language Learning English Journal, 2026)
Literal reading, which involves understanding information explicitly stated in a text, is a foundational component of reading comprehension and is essential for higher-level reading skills. Despite its importance, limited research has examined students’ challenges at this basic level of comprehension in the Indonesian EFL context. This research employed quantitative descriptive. The participants were 68 first-year university students enrolled in an English course at a university in Indonesia. Data were collected using a self-developed questionnaire consisting of eight Likert-scale. The findings reveal that many students experience persistent difficulties in literal reading comprehension. High proportions of neutral responses across items indicate uncertainty and inconsistent confidence in processing explicitly stated information in English texts. Difficulties were particularly evident in sentence-level comprehension, identifying textual relationships, and verifying information based on clear textual evidence. Although understanding basic WH-information appeared less problematic, students’ overall literal reading skills remained unstable. The conclusion is that literal reading skills cannot be assumed to be fully developed among university-level EFL learners. Explicit instruction, targeted vocabulary support, and structured reading activities are recommended to strengthen students’ foundational reading comprehension.